ECONOMIC AND FISCAL DETERMINANTS OF PUBLIC DEBT IN TÜRKİYE: EVIDENCE FROM STRUCTURAL BREAK COINTEGRATION ANALYSIS (1990-2024) - Köstekçi, Ahmet (Kütahya Dumlupinar University, 2025)
Determining the dynamics affecting the public debt portfolio, which is the largest fiscal portfolio of a country, plays a critical role in ensuring both macroeconomic stability and a sustainable fiscal structure. In this sense, this study aims to examine the main economic and fiscal dynamics driving public debt Türkiye for the period 1990-2024. As indicated by the results of the Maki (2012) multiple structural break cointegration test conducted to examine the cointegration relationship, it is found that there is a long-run relationship between the variables. According to the FMOLS and DOLS long-run coefficient estimation results, inflation and unemployment have a positive effect on the public debt burden, while economic growth and improvements in the primary budget balance reduce the public debt burden. In particular, it is concluded that the most powerful policy instrument for a sustainable fiscal structure is the primary budget balance, which shows the fiscal position of the state. The findings of the study suggest that institutional arrangements that support the economic growth process, the fight against inflation, policies to reduce unemployment, a consistent understanding of fiscal consolidation, and budget policies that observe fiscal discipline are necessary policy instruments for a sustainable public debt structure.

Bir ülkenin en büyük finansal portföyü olan kamu borç portföyünü etkileyen dinamiklerin belirlenmesi hem makroekonomik istikrarın sağlanmasında hem de sürdürülebilir mali yapının oluşturulmasında kritik bir rol almaktadır. Bu anlamda çalışma, 1990-2024 dönemi için Türkiye'de kamu borçlanmasına yön veren temel ekonomik ve mali dinamikleri belirlemeyi amaçlamaktadır. Eşbütünleşme ilişkisinin incelenmesi amacıyla yapılan Maki (2012) çoklu yapısal kırılmalı eşbütünleşme testi sonuçlarına göre, değişkenler arasında uzun dönemli bir ilişkinin olduğu tespit edilmiştir. FMOLS ve DOLS uzun dönem katsayı tahmin sonuçlarına göre, enflasyon ve işsizlik kamu borç yükü üzerinde pozitif yönlü etkiler yaratırken, ekonomik büyüme ve birincil bütçe dengesindeki iyileşmeler ise kamu borç yükünü azaltmaktadır. Özellikle sürdürülebilir mali yapı için en güçlü politika aracının, devletin mali pozisyonunu gösteren birincil bütçe dengesi olduğu sonucuna ulaşılmıştır. Çalışmadan elde edilen bulgular, ekonomik büyüme sürecini destekleyen kurumsal düzenlemelerin, enflasyonla mücadelenin, işsizliği azaltmaya dönük politikaların ve mali konsolidasyona ilişkin tutarlı bir anlayış ile mali disiplini gözeten bütçe politikalarının sürdürülebilir kamu borç yapısı için gerekli birer politika aracı olduğunu göstermektedir.
TÜRKİYE’DE KAMU BORCUNUN EKONOMİK VE MALİ BELİRLEYİCİLERİ: YAPISAL KIRILMALI EŞBÜTÜNLEŞME ANALİZİNDEN KANITLAR (1990-2024)
Keywords: Policy of Treasury; Maliye Politikası